Wideband tympanometry and otoacoustic emissions in children with risk factors for hearing loss (Research, Society and Development, 2023)
Introduction: Wideband tympanometry and evoked otoacoustic emissions can help audiologically monitor children birth to 3 years old, with or without risk factors for hearing loss. Objective: To study wideband tympanometry results in acoustic absorbance measures and transient evoked and distortion-product otoacoustic emission records during audiological monitoring. Method: This prospective observational study encompassed 58 children with and without risk indicators for hearing loss, with a mean age of 16.7 months. Data were obtained from the databases of four public maternity hospitals in São Paulo. Subjects were characterized as normal hearing or conductive hearing loss in the groups with and without risk factors for hearing loss. Results: Wideband absorbance at 1000 to 8000 Hz was verified to correlate the absorbance level with the transient evoked and distortion-product otoacoustic emission response levels at 1000 to 8000 Hz and wideband tympanometry. Normal hearing individuals’ absorbance at 1500 Hz to 6000 Hz ranged from 0.92 to 0.98, in which the best results may be found. Conclusion: Absorbance values are higher in male and normal hearing children. Evoked otoacoustic emission levels agreed with absorbance measures – the greater the absorbance, the higher the transient evoked and distortion-product otoacoustic emission levels.